1982
DOI: 10.1016/s0006-3495(82)84690-0
|View full text |Cite
|
Sign up to set email alerts
|

Solvent substitution as a probe of channel gating in Myxicola. Effects of D2O on kinetic properties of drugs that occlude channels

Abstract: The effects of solvent substitution on the steady-state and kinetic properties of drugs (gallamine triethiodide) and ions (nonyltriethylammonium and Ba++) known to occlude Na+ and K+ channels have been examined and compared with the effects of D2O on unmodified channels. In general, we observed large isotope effects on the kinetics of occlusion at temperatures of 5 degrees C, but only minor effects at 15 degrees C, consistent with processes involving significant solvent interaction. Steady-state behavior was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 35 publications
4
22
0
Order By: Relevance
“…The fast components of these traces now overlie with no apparent dissimilarities in their rates. However, we also noticed (as did Schauf and Bullock [1982] from Myxicola) that when…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…The fast components of these traces now overlie with no apparent dissimilarities in their rates. However, we also noticed (as did Schauf and Bullock [1982] from Myxicola) that when…”
Section: Resultssupporting
confidence: 56%
“…Schauf and Bullock (1982) also reported that the sodium channel tail current was apparently insensitive to the solvent effects. They noticed that when the tail current records in H20 and D20 were scaled and superimposed, the fast components were identical while the slower components showed slight sensitivity or variability in D20.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As was described previously, the H/D ratio in conductance of Na + is 1.35 (Schauf & Bullock, 1982). Different from other ionic currents, when the Na + channel is abruptly depolarized, a small outward current precedes the Na + current.…”
Section: Na + Channelsupporting
confidence: 53%
“…For example, voltage-dependent Na channels of rabbit muscle activate 2.3 times faster and inactivate 3.4–9.1 times faster upon a 10°C temperature increase in the range of 0 to 22°C [22]. Within a similar temperature range, the rates of Myxicola axon voltage-dependent K channel activation and inactivation were estimated to be 2.4 and 3.0 times, respectively, faster [30]. Assuming similar Q 10 values for the rat hippocampal neuron voltage-dependent Na and K channels, we expect their activities to increase by 52–202% (for Na channel) and 55–73% (for K channel) upon 500 ms irradiation of the CNI-laser used in this study.…”
Section: Discussionmentioning
confidence: 99%